لقانون المنطبق على استخدام الطائرات المسلحة بدون طيار (الدرون) في زمن النزاعات المسلحة - معماش, صلاح الدين (جامعة الوادي.University eloued, 2022)
تطغى هذه الأيام نزعة استخدام الطائرات بدون طيار بجميع أنواعها وأحجامها وقدراتها الخارقة، ضد المواقع العسكرية الهامة والأهداف المدنية كالمطارات، وفي مقابل استخدام هذه التكنولوجيا الحديثة، يجهل أطراف النزاع ما هو الإطار القانوني الذي ينظم استخدامها، ويحمي الضحايا، وعندما تتسبب في انتهاكات جسيمة للقانون الدولي الإنساني، ومتى يتعرض مشغلوها للمساءلة المباشرة، والتي يرجع أمر المقاضاة عنها إلى الدول ذات السيادة. ويعكس هذا المقال، إمكانية تطبيق القانون الدولي الإنساني على هذه الظاهرة الجديدة، ليس باعتباره وسيلة لمواجهة فضائع الحرب فحسب، بل لكونه الأبرز فيما يتصل بالحروب الأهلية والدولية، واستخدام الأسلحة المفضية إلى الإصابات المفرطة أو الآلام التي لا مبرر لها، ومنها الطائرات بدون طيار، فضلا عن تقريره لشرعية ومشروعية استخدامها. Abstract: Nowadays, the tendency to use drones of all types, sizes and capacities against important military sites and civilian targets such as airports prevails In exchange for the use of this modern technology, the parties to the conflict ignore the framework legal framework that regulates their use, protects victims, and when they cause serious violations of international humanitarian law, and when their operators are directly responsible, which it is up to sovereign States to prosecute. This article reflects the possibility of applying international humanitarian law to this new phenomenon, not only as a means of dealing with the atrocities of war, but also because it is most important with regard to civil and international wars, and the use of weapons that lead to excessive injury or undue pain, including drones, as well as for its report on the legality and licitness of its use.
Keywords: الطائرات بدون طيار ; القانون الدولي الإنساني ; النزاعات المسلحة الدولية وغير الدولية ; التمييز ; التناسب ; الإرهاب ; الجرائم; Drones; international humanitarian law ; international and non-international armed conflicts, discrimination ; proportionality ; terrorism ; crimes